Immunological status in broiler chickens vaccinated with newcastle vaccine and treated with cephradine - Elkomy, Ashraf; Aboubakr, Mohamed; Elsayed, Faten; Emam, Elsayed; Kassem, Mohammed (International Journal of Pharmacology and Toxicology, 2019)
The objective of this study is to clarify the effect of cephradine on cellular and humeral immune responses in broiler chickens. One hundred one-day-old Hubbard broiler chicks were divided into four equal groups (25 chicks in each). 1st group healthy broiler chickens non-vaccinated non medicated (control group), 2nd healthy broilers vaccinated with Newcastle vaccine only, 3rd group healthy broilers received 20 mg cephradine in drinking water daily for 5 consecutive days and 4th group healthy broilers vaccinated and received 20 mg/kg b.wt cephradine daily for 5 consecutive days. At 1st, 10th and 20th day post administration, blood samples were collected for determination total and differential leucocytic count, phagocytic activity, index, killing percentage and HI titer. Vaccinated broilers by Newcastle disease virus vaccine only, showed insignificant increase in leukocytic count, lymphocyte, heterophils, nitric oxide, lysozyme activity, total protein, total, Î³ globulin and HI titers at 1st day post vaccination. Beside significant increase at 10th and 20th day post vaccination coupled with insignificant increase in eosinophils, basophils, monocyte, phagocytic activity, phagocytic index, killing %, albumin and Î± globulin and non-significant decrease in serum Î² globulin and A/G ratio allover experimental periods post vaccination. Broilers received cephradine and/or vaccinated with Newcastle vaccineeither alone or together, showed insignificant increase in leukocyte, heterophils, lymphocyte, eosinophils, basophils, monocyte, nitric oxide, lysozyme activity, total protein, albumin, total, Î±, Î², Î³ globulin, A/G ratio throughout experimental period post vaccination. Beside significant decrease in phagocytosis, phagocytic index and killing % at 1st day and insignificant decrease at 10th & 20th day post vaccination coupled with significant decrease in HI titers at 1st day post administration and insignificant decrease at 10th & 20th day post vaccination. It was concluded that vaccination by Newcastle disease virus vaccine induced immune-stimulant but cephradine provoked a remarkable immunosuppressive effect in broiler chickens. Therefore, vaccination not recommended during treatment by cephradine.Â Â